Hydrophilization of the polyethyleneterephthalate ion track membrane surfaces. Issue 1 (June 2021) - Melnikova, G B; Salamianski, A E; Korolkov, I V; Tolstaya, T N; Akulova, V M; Chizhik, S A; Zdorovets, M V; Muslimova, I B; Kotov, D V
Abstract: Results of polyethylenterephtalate ion track membranes hydrophilization by (Chytozan/Dextran)4 multilayers with using Layer-by-Layer method and by Nafion monolayer with using Langmuir – Blodgett and spin-coating methods are presented in articles. The structure, contact angles and polar component of specific surface energy of modified membranes has been researched.